(untitled) (Clinics, 2021)
Breast cancer is the most frequently diagnosed malignant neoplasm in women and is considered a multifactorial disease of unknown etiology. One of the major risk factors is genetic alteration. Changes in CYP19A1 gene expression levels have been associated with increased risk and increased aggressiveness of breast cancer. Increased CYP19A1 gene expression and/or aromatase activity are among the major regulatory events for intratumoral production of estrogens in breast malignant tissues. This systematic review aimed to investigate the influence of CYP19A1 gene expression levels in women with breast cancer. The research was carried out using the PubMed, Scopus, and Web of Science databases. Searches were conducted between February 2 and May 15, 2019. Inclusion criteria were studies published between 2009 and 2019, English language publications, and human studies addressing the gene expression of CYP19A1 in breast cancer. A total of 6.068 studies were identified through PubMed (n=773), Scopus (n=2,927), and the Web of Science (n=2,368). After selecting and applying the inclusion and exclusion criteria, six articles were included in this systematic review. This systematic review provides evidence that increased or decreased levels of CYP19A1 gene expression may be related to pathological clinical factors of disease, MFS, OS, DFS, WATi, markers of metabolic function, concentrations of E1, FSH, and in the use of multiple exons 1 of the CYP19A1 gene in breast cancer.